Household carriage and acquisition of extended-spectrum β-lactamase–producing Enterobacteriaceae: A systematic review. (11th March 2020) - Martischang, Romain; Riccio, Maria E.; Abbas, Mohamed; Stewardson, Andrew J.; Kluytmans, Jan A. J. W.; Harbarth, Stephan
Abstract: Objective: The epidemiology of ESBL-producing Enterobacteriaceae (ESBL-PE) has been extensively studied in hospitals, but data on community transmission are scarce. We investigated ESBL-PE cocarriage and acquisition in households using a systematic literature review. Methods: We conducted a systematic literature search to retrieve cross-sectional or cohort studies published between 1990 and 2018 evaluating cocarriage proportions and/or acquisition rates of ESBL-PE among household members, without language restriction. We excluded studies focusing on animal-to-human transmission or conducted in nonhousehold settings. The main outcomes were ESBL-PE cocarriage proportions and acquisition rates, stratified according to phenotypic or genotypic assessment of strain relatedness. Cocarriage proportions of clonally related ESBL-PE were transformed using the double-arcsine method and were pooled using a random-effects model. Potential biases were assessed manually. Results: We included 13 studies. Among 863 household members of ESBL-PE positive index cases, prevalence of ESBL-PE cocarriage ranged from 8% to 37%. Overall, 12% (95% confidence interval [CI], 8%–16%) of subjects had a clonally related strain. Those proportions were higher for Klebsiella pneumoniae (20%–25%) than for Escherichia coli (10%–20%). Acquisition rates of clonally related ESBL-PE among 180 initially ESBL-PE–free household members of a previously identified carrier ranged between 1.56 and 2.03 events per 1, 000 person weeks of follow-up. We identified multiple sources of bias and high heterogeneity (I 2, 70%) between studies. Conclusions: ESBL-PE household cocarriage is frequent, suggesting intrafamilial acquisition. Further research is needed to evaluate the risk and control of ESBL-PE household transmission.